Policy mixes for incumbency: Exploring the destructive recreation of renewable energy, shale gas 'fracking, ' and nuclear power in the United Kingdom. (November 2017) - Johnstone, Phil; Stirling, Andy; Sovacool, Benjamin
Abstract: The notion of a 'policy mix' can describe interactions across a wide range of innovation policies, including 'motors for creation' as well as for 'destruction'. This paper focuses on the United Kingdom's (UK) 'new policy direction' that has weakened support for renewables and energy efficiency schemes while strengthening promotion of nuclear power and hydraulic fracturing for natural gas ('fracking'). The paper argues that a 'policy apparatus for incumbency' is emerging which strengthens key regime-based technologies while arguably damaging emerging niche innovations. Basing the discussion around the three technology-based cases of renewable energy and efficiency, fracking, and nuclear power, this paper refers to this process as " destructive recreation ". Our study raises questions over the extent to which policymaking in the energy field is not so much driven by stated aims around sustainability transitions, as by other policy drivers. It investigates different 'strategies of incumbency' including 'securitization', 'masking', 'reinvention', and 'capture.' It suggests that analytical frameworks should extend beyond the particular sectors in focus, with notions of what counts as a relevant 'policy maker' correspondingly also expanded, in order to explore a wider range of nodes and critical junctures as entry points for understanding how relations of incumbency are forged and reproduced.